2006
DOI: 10.1042/bj20051708
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cross-reactivity and of the 1.5 Å crystal structure of the Malassezia sympodialis Mala s 6 allergen, a member of the cyclophilin pan-allergen family

Abstract: Cyclophilins constitute a family of proteins involved in many essential cellular functions. They have also been identified as a panallergen family able to elicit IgE-mediated hypersensitivity reactions. Moreover, it has been shown that human cyclophilins are recognized by serum IgE from patients sensitized to environmental cyclophilins. IgE-mediated autoreactivity to self-antigens that have similarity to environmental allergens is often observed in atopic disorders. Therefore comparison of the crystal structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 36 publications
2
72
0
1
Order By: Relevance
“…Therefore it can be concluded that the Asp f 9 cDNA sequence is correct, and that the published Asp f 16 peptide sequence results from frameshift, other sequencing errors, or derives from a different A. fumigatus strain; (iii) Asp f 17, originally described as a cDNA encoding a 191 amino acid protein [24], is incomplete and the complete gene encodes a protein of 284 amino acids; and (iv) the postulated sequence of the Asp f 56 kDa allergen not included in the official allergen database, which was derived from a short peptide obtained from a biochemically purified protein [28] is not predicted to be encoded in any of the sequenced Aspergillus genomes. All other A. fumigatus allergens reported in the official allergen database as well as the sequences of the recently cloned thioredoxins (Asp f 28, Asp f 29) [29], cyclophilins (Asp f 11, Asp f 27) [30], and Phi A cell wall protein (Asp f 34, Glaser unpublished) sequences showed virtually a 100% identity with the genome sequence, confirming at genomic level the validity of cDNA cloning approaches for the elucidation of allergen repertoires. The whole repertoire of A. fumigatus allergens included in the official allergen list reported in Table 2 have been produced as highly pure recombinant allergens and evaluated for their IgE-binding capacity in vitro.…”
Section: The Allergen Repertoire Of Aspergillus Fumigatusmentioning
confidence: 83%
See 4 more Smart Citations
“…Therefore it can be concluded that the Asp f 9 cDNA sequence is correct, and that the published Asp f 16 peptide sequence results from frameshift, other sequencing errors, or derives from a different A. fumigatus strain; (iii) Asp f 17, originally described as a cDNA encoding a 191 amino acid protein [24], is incomplete and the complete gene encodes a protein of 284 amino acids; and (iv) the postulated sequence of the Asp f 56 kDa allergen not included in the official allergen database, which was derived from a short peptide obtained from a biochemically purified protein [28] is not predicted to be encoded in any of the sequenced Aspergillus genomes. All other A. fumigatus allergens reported in the official allergen database as well as the sequences of the recently cloned thioredoxins (Asp f 28, Asp f 29) [29], cyclophilins (Asp f 11, Asp f 27) [30], and Phi A cell wall protein (Asp f 34, Glaser unpublished) sequences showed virtually a 100% identity with the genome sequence, confirming at genomic level the validity of cDNA cloning approaches for the elucidation of allergen repertoires. The whole repertoire of A. fumigatus allergens included in the official allergen list reported in Table 2 have been produced as highly pure recombinant allergens and evaluated for their IgE-binding capacity in vitro.…”
Section: The Allergen Repertoire Of Aspergillus Fumigatusmentioning
confidence: 83%
“…However, only three crystal structures derived from fungal allergens, ribotoxin (Asp f 1) [45, 46], MnSOD (Asp f 6) [65] from A. fumigatus and a Xylanase from Paecilomyces variotii [66] have been reported so far. Recently the crystal structures of a cyclophilin of A. fumigatus (Asp f 11) [61] and Malassezia sympodialis (M. sympodialis) (Mala s 6) [30], as well as the crystal structure of thioredoxin of M. sympodialis (Mala s 13) [29], and Mala s 1, a major allergen of M. sympodialis with unknown function [67] have been determined at high resolution.…”
Section: Structural Aspects Of Fungal Allergensmentioning
confidence: 99%
See 3 more Smart Citations